If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-9+5(2x+12)=9(-2x+4)-14
We move all terms to the left:
-9+5(2x+12)-(9(-2x+4)-14)=0
We multiply parentheses
10x-(9(-2x+4)-14)+60-9=0
We calculate terms in parentheses: -(9(-2x+4)-14), so:We add all the numbers together, and all the variables
9(-2x+4)-14
We multiply parentheses
-18x+36-14
We add all the numbers together, and all the variables
-18x+22
Back to the equation:
-(-18x+22)
10x-(-18x+22)+51=0
We get rid of parentheses
10x+18x-22+51=0
We add all the numbers together, and all the variables
28x+29=0
We move all terms containing x to the left, all other terms to the right
28x=-29
x=-29/28
x=-1+1/28
| x+-8=-14 | | c1/4c=1/5 | | (3x-3)+51+(8x-66)=180 | | -5+m=-5* | | -8(r-6)=32 | | 13+(x-6=4x-7 | | 16(x+16-x)=470 | | -4(3x-6)=28 | | 3x+6=x+8+x | | 226=15x | | 200=10y | | 8(v-2)-5(v-7)=2v+11 | | (3x-3)+51(8x-66)=180 | | 8s-22=3(3s+11)-s | | 18=s+9 | | 15m+3=48 | | 30=180(n-2) | | 12.50x+45=7.50x+75 | | 0.4x=6.2x+1.2 | | F(-7)=3x-2 | | x+-4=-20 | | g/29=10 | | 5(1/2x+2)=3*(x-2) | | 7-s=84 | | 6-4x=x+1-10x | | (3x-4)=(7x-54) | | 12h=540 | | 28=–2m | | 3u(u-1)(u-2)=0 | | p-50=-10 | | 20x9=10x9 | | 81=81-7t |